Usability Analysis of Mobile Applications Used for Foreign Language Learning - Fatih Erdoğdu; Kübra Kırdar; Fatma Eski; Edanur Okumuş (International Journal of Pioneering Technology and Engineering)
The aim of this study is to evaluate the usability of mobile applications for learning foreign languages. The study examined the effectiveness, efficiency and user satisfaction of the selected applications. The research was conducted using a user-based approach and observed the behavior of real users while using the applications and collected their opinions. The study participants consisted of 10 university students. The participants were selected using the convenience sampling method. This method allowed researchers to quickly reach existing participants. Participants performed five different tasks using applications they had never used before. Applications included Duolingo, Cake and Memrise. In the efficiency dimension, Cake had the highest success rate (54%), while Duolingo had the lowest success rate (34%). In the efficiency dimension, Duolingo had the fastest task completion time, while Cake took the longest. In terms of user satisfaction, Cake received the highest satisfaction rating. Participants reported that Cake was easier to use due to its simple tasks and user-friendly interface. On the other hand, Duolingo's complex interface and repetitive structure made it difficult for users to use the application long-term. Overall, all applications were rated as moderately user-friendly. The study highlights the importance of user-centered design to increase the effectiveness of mobile language learning applications and provides insights into future research.